HOTEL ROOM RESERVATION APPLICATION IN PERMATA HOTEL USING VISUAL BASIC 6.0 - Ika Perminawati; Susi Wagiyati P, SKom, MMSI (Jurnal Sistem Informasi, 2003)
In the era of increasing globalization of computer technology. Particularly on the hospitality sector in which to provide the best service as well in order to boost its image in society at largeand can get the job done effectively and efficiently in particular. Then the author tries to make the reservation application, at Mulia Permata Hotel using Visual Basic 6.0. With Visual Basic application, the author tried to make programs for room reservations, guest list, payments and generate financial statements.The purpose of making reservation application with Visual Basic is to facilitate in obtaining information quickly in providing service to hotel guests, facilitate data storage and search procedures guest data and minimize the occurrence of errors in calculating the length of stay of the payment process of the hotel.